2016
DOI: 10.1088/1674-1056/25/8/080304
|View full text |Cite
|
Sign up to set email alerts
|

Quantum speed limits of a qubit system interacting with a nonequilibrium environment

Abstract: The speed of evolution of a qubit undergoing a nonequilibrium environment with spectral density of general ohmic form is investigated. First we reveal non-Markovianity of the model, and find that the non-Markovianity quantified by information backflow of Breuer et al. [Phys. Rev. Lett. 103 210401 (2009)] displays a nonmonotonic behavior for different values of the ohmicity parameter s in fixed other parameters and the maximal non-Markovianity can be achieved at a specified value s. We also find that the non-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Here, G x [ ] shows the Euler gamma function. It is important to note that unlike the thermal equilibrium case, this decoherence factor exhibits nonmonotonic decay for all values of Ohmicity parameter n [42,43]. Therefore, the non-equilibrium environment considered in our study has a non-Markovian feature for all kinds of Ohmic spectral densities (i.e., sub-Ohmic, Ohmic, and super-Ohmic).…”
Section: The Physical Model and Its Solutionmentioning
confidence: 78%
See 1 more Smart Citation
“…Here, G x [ ] shows the Euler gamma function. It is important to note that unlike the thermal equilibrium case, this decoherence factor exhibits nonmonotonic decay for all values of Ohmicity parameter n [42,43]. Therefore, the non-equilibrium environment considered in our study has a non-Markovian feature for all kinds of Ohmic spectral densities (i.e., sub-Ohmic, Ohmic, and super-Ohmic).…”
Section: The Physical Model and Its Solutionmentioning
confidence: 78%
“…Interestingly, in [40] it was shown that decoherence in a single-qubit system interacting with a non-equilibrium environment could be potentially controlled by manipulating the relative initial phases of the terms in the Fourier series (or equivalently relative initial phases of the reservoir's modes). Later, it was demonstrated that such a non-equilibrium dephasing environment with an Ohmic class spectrum has dominant effects on the geometric phase and quantum speed limit [41][42][43]. Remarkably, this engineered non-dissipative non-equilibrium environment exhibits non-Markovian characteristics for all the values of Ohmicity parameter n [42].…”
Section: Introductionmentioning
confidence: 99%
“…Many relevant physical systems, such as the quantum optical system, [3] the nanoscale solid-state quantum system, [4,5] quantum chemistry, [6] and the excitation transfer in the biological system, [7] should be treated by quantum non-Markovian processes. Recently, quantum non-Markovian processes have been studied extensively, from the measure of non-Markovianity of the processes [8][9][10][11][12][13][14][15][16][17][18] to the properties [19][20][21][22][23][24][25][26][27][28][29] and applications [30][31][32][33][34][35][36][37] of the dynamical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the appearance of definitions for QSLT in open quantum systems, the QSLT of quantum systems interacting with various environments has been widely investigated. [12][13][14] Recently, in order to obtain a faster speed of evolution, a lot of efforts have been made to short the QSLT. It has been suggested that memory environments can speed up quantum evolution and the mechanism of the acceleration in open quantum systems is related not only to the non-Markovianity but also to the population of excited states.…”
Section: Introductionmentioning
confidence: 99%